CONTRIBUTIONS TO MASTERY THE DRAWING BUILDINGS’ CONSTRUCTION TOWARDS THE LEARNING OUTCOME OF STUDENTS IN TGB SMK NEGERI 1 BUKITTINGGI BY USING SOFTWARE - 1883-1899 , Arif Rahman (Universitas Negeri Padang, 2016)
ABSTRACTThe background of this study cause by the low score of students in class XI Drawing Building Engineering in Drawing Buildings’ Constrution and Drawing by using software in 2015/2016. Aim of this research is to find out how wide the contribution of knowledge acquisition Drawing Buildings’ Construction towards the learning outcome of students in TGB SMK Negeri 1 Bukittinggi.Type of this research is a correlational study. The population of this research is 51 students of Drawing Building Engineering in XI class of SMK Negeri 1 Bukittinggi by using Total Sampling. The data used pimary data. It collected by using an objective test questions. Objective test conducted to determine the level of students in mastery the knowledge of Drawing Buildings’ Construction with 45 questions. Also, the outcomes of learning Drawing by using software as the secondary data. Analysis of the data consists of, (1) a description of the data (2) testing requirements analysis and (3) hypothesis test.Based on the analysis result, the coefficient of correlations (r=0.809) on the probability of 0,000 < Significant Alpha 0.05. Level of responden in mastery GBK is about 61,05% which has low category. The hypothesis proposal had received with the contribution in mastery Drawing Buildings’ Construction knowledege about 65,45% towards students outcome in learning Drawing by using software of XI class in TGB SMK Negeri 1 Bukittinggi.Keywords: Contributions, Mastery, Knowledge, Learning Outcome